1998
DOI: 10.1590/s0004-282x1998000300005
|View full text |Cite
|
Sign up to set email alerts
|

Normal cerebrospinal fluid values in full-term gestation and premature neonates

Abstract: -Results of cerebrospinal fluid (CSF) examinations from 77 high-risk neonates were reviewed. The mean CSF white cells (WBC) count was 4.5 cell/mm 3 , being two standard deviations above the mean 11.7 cells/ mm 3 in the full-term gestation neonate group; in the premature neonate one, the mean CSF WBC count was 5.1 cells/mm 3 , being two standard deviations above the mean 16.7 cell/mm 3 . PMNs (polymorphonuclear leukocytes) were present in less than 40% of those children, being the mean PMN percentage 4.2% and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…In studies that have excluded infants with "traumatic taps" (or nonbacterial illnesses), the mean number of white blood cells in uninfected preterm or term infants was consistently <10 cells/mm 3 . [44][45][46][47][48][49][50] Cell counts 2 standard deviations from the mean were generally less than 20 cells/mm 3 . 46 In a study by Garges et al, the median number of white blood cells in infants who were born at greater than 34 weeks' gestation and had bacterial meningitis was 477/mm 3 .…”
Section: Lumbar Puncturementioning
confidence: 92%
See 1 more Smart Citation
“…In studies that have excluded infants with "traumatic taps" (or nonbacterial illnesses), the mean number of white blood cells in uninfected preterm or term infants was consistently <10 cells/mm 3 . [44][45][46][47][48][49][50] Cell counts 2 standard deviations from the mean were generally less than 20 cells/mm 3 . 46 In a study by Garges et al, the median number of white blood cells in infants who were born at greater than 34 weeks' gestation and had bacterial meningitis was 477/mm 3 .…”
Section: Lumbar Puncturementioning
confidence: 92%
“…55 Protein concentrations in uninfected, term newborn infants are <100 mg/ dL. [44][45][46][47][48][49][50] Preterm infants have CSF protein concentrations that vary inversely with gestational age. In the normoglycemic newborn infant, glucose concentrations in CSF are similar to those in older infants and children (70%-80% of a simultaneously obtained blood specimen).…”
Section: Lumbar Puncturementioning
confidence: 99%
“…The initial search term was “cerebrospinal fluid,” which was then combined with “white blood cell” or “leukocytosis,” and either “neonate,” “infant” or “newborn.” Limits included “humans” and “English language.” Titles and abstracts of 300 articles were reviewed for relevance: 5 studies were found to be relevant 17, 21, 23, 25, 27. Nine additional studies were identified during review of the references of textbooks and published studies 14–16, 18–20, 22, 24, 26…”
Section: Methodsmentioning
confidence: 99%
“…However, few patients ≤56 days of age have been studied, and different ranges of reference values have been established as authors have used varying exclusion criteria. These past studies included children with traumatic lumbar puncture,14–20 seizures,17 sepsis,21 congenital infections19, 22 and very low birth weights 23…”
Section: Introductionmentioning
confidence: 99%
“…The poor difference between the CSF parameters of premature and full‐term newborns was noteworthy. Nonetheless, we have previously demonstrated that only the mean percentage neutrophil count and the mean protein concentration were significantly different when CSF parameters from premature and full‐term newborns were compared (10). Regarding aging, the total WBC count and the protein concentration are expected to decrease as of 4 weeks of age among full‐term newborns (11).…”
Section: Descriptive Analysis Of the Cerebrospinal Fluid Parameters Omentioning
confidence: 99%